Logistic Regression Analysis of Risk Factors for Stunting Among Toddlers Aged 24-59 Months in Southeast Sulawesi, Indonesia - Fitri Rachmillah Fadmi; Sri Mulyani; La Djabo Buton; Wa Ode Sitti Justin; Yeni Riza (Health Dynamics, 2025)
Background: Stunting in toddlers is a health problem that can hinder human development globally.This condition has the potential to increase the number of stunting toddlers for toddlers under five years of age. The purpose of the study was to analyze the risk factors for stunting in toddlers under five during the pandemic. Methods: This research is an analytical survey of case-control study design with a 1:1 ratio selected using a simple random sampling technique source of data from primary and secondary data collection. Bivariate analysis was performed using Odds Ratio and chi-square tests, and multivariate analysis was performed using binary logistic regression. Results: The results showed that the variables that had risk factors for stunting were history of infectious disease (OR=5.769; p=0.004), low birth weight (LBW) (OR=4.444; p=0.017), history of exclusive breastfeeding (OR=4.552; p=0.010), family income (OR=6.314; p-value =0.004), knowledge (OR=3.818; p= 0.002) and the most dominant risk factor is family income. Conclusion: Important to reduce stunting cases through cross-sectoral collaboration regarding the modification of health services according to the socioeconomic level of the community.